Dendrite‐free and Stable Zn‐ion Energy Storage Devices Enabled by a Three‐dimensional Sn−Cu Foam Hosted Zn Anode. Issue 4 (13th March 2023) - Liang, Yiqi; Wang, Jun; Tian, Zhidong; Shang, Kezheng; Hu, Xiang; Yu, Jiaqi; Cai, Pingwei; Liu, Yangjie; Yuan, Jun; Ding, Yichun; Wen, Zhenhai
Abstract: Zn ion energy storage devices have received widespread attention because of their high safety, environmental friendliness, low cost, and high energy density. However, Zn metal anodes usually suffer from disadvantages such as dendrite growth, low coulombic efficiency, and volume expansion during plating/stripping, which severely hampers the practical applications. Here, we construct 3D Zn frameworks by exploring different conductive hosts and modify 3D hosts by plating Sn to suppress Zn dendrites and side reactions. The electrode which optimized by electroplating Zn after chemically plating Sn on Cu foam (Sn−Cu foam@Zn) exhibits stable polarization voltage distribution and almost 100% coulombic efficiency over 200 cycles of Zn plating/stripping. Furthermore, when pairing with V2 O5 cathode, the full cell showed fast reaction kinetics and a capacity of 113 mAh g −1 after 1000 cycles at a current density of 1 A g −1, which is 90.4% of the initial capacity. This work provides a new strategy for the development of high‐performance Zn anodes. Abstract : The development of Zn ion energy storage devices is seriously hindered by the drawbacks of dendrite growth, low coulomb efficiency, and volume expansion in the plating/stripping process of Zn metal electrodes. In this paper, the electrode which optimized by chemically plating Sn on Cu foam with high surface area and high HER overpotential can provide a large number of active sites for homogeneous nucleation of Zn metal and alleviate HER side reactions, thus improving the reversibility of Zn electrodeposition.